Beneficios de la canoterapia para el desarrollo motor en niños de 2 a 4 años con Síndrome de Down, 2018 - Inca Robalino, Darío David (2018)
The research work was developed with the compilation of bibliographic reviews found in different databases, with the objective of determining the benefits of canotherapy to improve motor development in children aged 2 to 4 years with Down Syndrome as a document to help the insertion in society. Improving the quality of life of the child and its environment, where we worked with four articles by several authors previously evaluated by the PeDro scale obtaining a good methodological quality, these studies have an age range of 1 to 13 years, where positive results of the use of canotherapy were defined in children with Down syndrome. A relevant statistical data is the study of Eloy P. Pineda in 2016 where a can is part of the therapy, the acquisition of new skills in learning was obtained from 47% to 85% in the motor skills of a 45% even 86% and socially from 38% to 56%. Performing sessions of 40 minutes once a week, for 1 year 6 months. Finally, as a global result it could be proved that the can being part of the therapy of the child with Down syndrome improves the motor development and provides several benefits for their physical and mental health.